Analysis Of Biology Problems In Grade X Science Textbooks Based On Bloom's Taxonomy On Anderson's Revision And Communication Skills - Mela Yayu Apriangi; Hadiansah Hadiansah; Epa Paujiah (Riviera Publishing, 2025)
Study This analyze problem biology in class X science book based on Anderson's revised Bloom's Taxonomy and skills communication students. Challenges learning the 21st century demands development think critical and communication, but majority question in book text Still focuses on Lower Order Thinking Skills (LOTS). Research aiming evaluate conformity question with dimensions cognitive Bloom's Taxonomy and identifying support to skills communication. Research This use approach quantitative descriptive with analyze question in book text based on LOTS and Higher Order Thinking Skills (HOTS) categories, as well as supporting elements? communication scientific. Research result show that 66.32% of the questions in virus chapter and 72.29% of questions in chapter diversity creature life is at in LOTS category, with domination level cognitive remembering (C1) and understanding (C2). The proportion of HOTS, such as analysis (C4) and creation (C6), very low, indicating limitations in facilitate think critical. Support to skills communication is also minimal, limited to discussion simple without strengthening presentation or debate. Study This highlight the need improvement amount question HOTS based and enrichment element communication in book text For support learning holistic. Findings This give implications important for development more teaching materials balanced and relevant with demands Independent Curriculum. Books text expected can push student For think critical, creative, and communicative, supporting scientific literacy in the era of modern learning.